Konsep Pendidikan Hadhari di Pondok Pesantren Darullughah Wadda’wah Bangil-Pasuruan - Unun Zumairoh Asr Himsyah; Asep Rahmatullah (Al-Jadwa: Jurnal Studi Islam, 2021)
ABSTRACT Pesantren is a non-formal educational institution that carries the educational mandate of the Qur'an and Hadith. In the process of organizing in Islamic boarding schools, it is required to be able to answer the needs of the times. Thus making the pesantren change its identity into a modern and salaf pesantren. Salaf Islamic boarding schools are characterized by the existence of diniyah education, and modern education is characterized by formal education ranging from basic education to tertiary education (Madrasah Ibtidaiyah/MI, Madrasah Tsanawiyah/MTs, Madrasah Aliyah/MA, S1, S2 and S3). Pesantren uses an integrated curriculum of three entities, firstly hadharah an nash, second hadharah falsafi, and third hadharah al 'ilm. The development of branches and structures of hadith scholarship is currently oriented to philosophy and ethics, ranging from social sciences, natural sciences to the humanities, or in the Islamic scientific scheme includes the revealed knowledge, namely the religious sciences, and the sciences. learned rationally, this concept is known as hadhari education. By using descriptive qualitative research methods through a phenomenological approach to review the concept and system of hadhari education implemented at the Darullughah Wadda'wah Islamic Boarding School in general. It is hoped that the results of this study will increase public knowledge about the concept and system of hadhari education by developing fields of scientific study. Keywords: Concept, Education, Hadhari